A randomized, double-blinded, placebo-controlled, single dose analgesic study of preoperative intravenous ibuprofen for tonsillectomy in children - Cui, Xiaohuan; Zhang, Jianmin; Gao, Zhengzheng; Sun, Lan; Zhang, Fuzhou (Frontiers in Pediatrics, 2022)
Purpose Tonsillectomy is a recognized treatment for children with tonsil hypertrophy and results in significant postoperative oropharyngeal pain. Fentanyl and other morphine-like analgesics are widely used as perioperative analgesia but are associated with side effects such as vomiting, nausea, and respiratory depression. As the least toxic non-steroidal anti-inflammatory drug, ibuprofen may be effective and safe for pain control after tonsillectomy. We aimed to explore whether the addition of intravenous (IV) ibuprofen administered at induction can reduce the need for early postoperativeanalgesics. Study design and methods This randomized, double-blind, controlled clinical trial enrolled 95 pediatric patients who underwent tonsillectomy. Participants aged 6 months to 12 years were randomly assigned to either the experimental and control groups (1:1). The children were premedicated 15 min before surgery with IV ibuprofen 10 mg kg−1 or placebo (normal saline). Pain was scored at 15, 30, and 120 min after extubation, and IV fentanyl (0.5 mcg kg−1) was administered when the Faces, Legs, Activity, Cry, and Consolability (FLACC) Scale was ≥7 and deemed appropriate by the nursing staff in the post-anesthesia care unit (PACU). The visual analog scale was used as a supplementary evaluation for older children (≥7 years old) who were awake and could self-report pain. The primary outcome variable was the number of patients who received postoperative analgesia. Results The requirement for rescue fentanyl was reduced by 18% with the addition of IV ibuprofen (P = 0.043). There were no signficant differences in the amount of fentanyl administered postoperatively (P = 0.127). Compared with the placebo group, the number of children who needed more than one dose of rescue fentanyl decreased in the experimental group, but the differences were not significant (P = 0.056). There were no significant differences between the groups in terms of operative blood loss (P = 0.978), vomiting, or postoperative bleeding (P = 0.474). Conclusion It is safe to administer IV ibuprofen 15 min before tonsillectomy, and it can significantly reduce the need for rescue fentanyl. IV ibuprofen should be considered as an important part of the multimodal approach for postoperative analgesia in children. Clinical trial registration Chictr.org.cn, identifier: ChiCTR2100044508.